Comparative Histological and Histochemical study of Corpora amylacea in the Mammary glands of Goats and Ewes - Shilpa S Modekar (Indian Journal of Veterinary Anatomy, 2026)
When it comes to the study of the process of tissue regression, the mammary gland is one of the most important and unique, organs which can be considered as the best experimental model. In each and every cycle of pregnancy and lactation, this gland undergoes massive expansion of the milk-producing secretory epithelium coupled with regression of adipocytes followed by reversal of this process during involution. The functional stage of mammary gland affects the incidence and distribution of corpora amylacea. Corpora amylacea were present in the mammary glands of both the small ruminants under investigation. Corpora amylacea occurred most frequently in the ewe, and were seen comparatively more in non-lactating mammary glands when compared with that of goat. In lactating stage these were situated mostly in the alveolus. During gestation they were located outside of the alveolus and in the interalveolar connective tissue. Only in very few cases corpora amylacea were found inside and outside of the alveolus in the same mammary gland. Their origin appeared to be cellular and the desquamated and infiltrated cells accumulate in the lumen became fragmented, degenerated and lysed to form a solid lump like structure.